Etika Pelayanan Akademik di Program Studi Hukum Bisnis ITBM Balik Diwa - Muhammad Luthfi Siraj; Suprianto Suprianto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
This study aims to analyze the academic service ethics of employees at the Balik Diwa Institute of Business and Maritime Technology (ITBM), focusing on three main dimensions: integrity, loyalty, and fairness. Academic service ethics are crucial in creating student satisfaction as users of educational services. This study used a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. Data analysis was conducted using an interactive model that includes data condensation, data presentation, as well as drawing conclusions and verification. The results show that the academic service ethics at ITBM Balik Diwa are quite good, but there are still several weaknesses. In the integrity dimension, employees have demonstrated courage in enforcing regulations, but there is still a sense of bias. In the loyalty dimension, employees demonstrate a love for their work and loyalty to the institution, although coordination between employees needs to be improved. In the justice dimension, employees are generally fair, but are still less open to student complaints, which is why ITBM Balik Diwa urgently needs continuous evaluation and development to strengthen academic service ethics so that services to students are more professional and with high integrity